Use Box –PCR to Study Genetic Relatedness of Some Pseudomonaus aeruginosa Isolates from Different Clinical and Environmental Sources In Baghdad (Journal of the College of Basic Education, 2022)
Summary Totally twenty six different isolates of Pseudomonas aeuruginosa ( P. aeruginosa ) were collected ,sixteen clinical isolates ( 62% of total group ) were isolated from different samples ( Urine , blood , sputum , wound , ear , eye and throat swabs ) from Medical city hospital in Baghdad, and ten environmental isolates ( 38% of total group ) were isolates from different places of soil and water in the same city . All isolates were diagnosed by bacteriological and biochemical tests . The crude DNA was extracted from all clinical and environmental isolates . BOX-PCR was achieved using BOX1AR primer . The BOX-PCR products were analyzed by horizontal agarose gel electrophoresis . The dendrogram for all isolates was draw by using band-based Jaccard and Dice coefficients where the fingerprints were generated by banding patterns using un weighted pair-group method with arithmetic average ( UPGMA ) , in order to study the relatedness among the clinical and environmental isolates . The results were showed that the crude DNA was suitable to BOX-PCR , and presence of the high similarity in banding patterns of clinical and environmental isolates itselves , which was about 45%-99% and 61%-100% in Jaccard and Dice coefficients respectively . The similarity between these two groups was about 40% and 55% in Jaccard and Dice coefficients respectively . Although , the marked relatedness among all clinical and environmental isolates , this study was concluded presence of genetic variation between the clinical and environmental isolates of this opportunistic bacterium , by using BOX-PCR technique and BOX1AR primer